Urinary 8-hydroxy-2′-deoxyguanosine as a novel biomarker of inflammatory activity in patients with cardiac sarcoidosis. (1st July 2015) - Kobayashi, Shigeki; Myoren, Takeki; Oda, Seiko; Inari, Makana; Ishiguchi, Hironori; Murakami, Wakako; Fukuda, Masakazu; Tanaka, Takeo; Okuda, Shinichi; Nao, Tomoko; Doi, Masahiro; Yamada, Jutaro; et al.
Abstract: Background: Inflammation and oxidative stress play a crucial role in the pathogenesis of cardiac sarcoidosis (SAR). We investigated whether urinary (U) 8-hydroxy-2′-deoxyguanosine (8-OHdG)—an oxidative DNA damage marker—was related to SAR inflammatory activity. Methods: U-8-OHdG levels were measured in 31 SAR patients, classified as active (n = 17) or non-active (n = 14) based on 18 F-fluorodeoxyglucose positron emission tomography–computed tomography ( 18 F-FDG-PET/CT), 28 dilated cardiomyopathy (DCM) patients, and 30 controls. In active SAR patients, U-8-OHdG levels were reexamined and compared with 18 F-FDG-PET/CT results at 6 months after corticosteroid treatment to assess therapeutic response. Results: Immunohistochemical examination of left ventricle (LV) autopsy samples from SAR patients revealed positive 8-OHdG staining in cardiomyocyte nuclei from LV sections showing 18 F-FDG accumulation on PET/CT, while serum 8-OHdG levels were significantly higher in the coronary sinus than in the aortic root only in active SAR patients. U-8-OHdG levels in SAR patients were higher than those in controls, and significantly higher in active SAR patients than in non-active SAR and DCM patients. U-8-OHdG was a powerful predictor of active SAR in receiver operating characteristic curve analysis (AUC, 0.98; 95% CI, 0.94–1.02; optimal cutoff value, 13.1 ng/mg creatinine), with a sensitivity of 88.2% and a specificity of 92.9%. U-8-OHdG levels in responders significantly decreased at 6 months after corticosteroid treatment initiation, in proportion with the decrease in the focal cardiac uptake of 18 F-FDG. Conclusions: U-8-OHdG is a potentially clinically useful biomarker for evaluating inflammatory activity and monitoring the effectiveness of corticosteroid therapy in SAR patients. Highlights: Myocardial oxidative stress is elevated in cardiac sarcoidosis (SAR). U-8-OHdG is largely derived from cardiac tissue. U-8-OHdG levels represent the inflammatory activity of SAR. U-8-OHdG is a novel biomarker for the diagnosis and the treatment of SAR.